I've been stuck on this question for the better part of the day, and I've succumbed to asking for help. I'm not sure how to go about it honestly. I've tried to do the contrapositive to prove it, but I get stuck and end up at a dead end.
The problem is as follows: $$ [(\forall y \forall z \space p(y,z)) \space \vee \space (\exists z \forall y \space q(y,z))] \space \to \space \forall y\exists z(p(y,z) \space \vee \space q(y,z)) $$
I'm supposed to to prove this is valid using interpretations. I can not replace the implies either.